Factores pronósticos de morbimortalidad cardiovascular en pacientes egresados con infarto agudo al miocardio seguidos por un año - Ugalde P., Héctor; Cifuentes R., Ignacio; Romero A., Pablo; Castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2019)
Acute myocardial infarction is one of the main causes of death in the world, this occurs in the in-hospital period as well as in the follow-up. It has been much studied what occurs in the in-hospital period, but much less what occurs in the follow-up of patients with this pathology. The objective of this study was to follow patients discharged after myocardial infarction for 1 year and analyze predictors of cardiovascular events. 1174 patients were followed for 1 year, of which 17% presented some serious cardiovascular event, associated with the presence of male sex, older age, arterial hypertension, previous history of angina, hospital treatment only pharmacological, inclusion of positive inotropes in the initial treatment and use of calcium channel blockers, factors already shown by international literature but less analyzed in our country, and furthermore, the demonstration that invasive management with coronary angioplasty or bypass surgery are protective factors of the occurrence of events in this period, which reinforces the idea of a more intensive and invasive management in patients with this pathology.